Bryophilous Agaricales in Southern Brazil - Cassiane Furlan-Lopes; Alice Lemos Costa; Ana Luiza Klotz-Neves; Kamille Rodrigues Ferraz; Fernando Augusto Bertazzo-Silva; Jorge Renato Pinheiro Renato Pinheiro Velloso; Jair Putzke (Acta Biológica Catarinense, 2023)
Bryophytes colonize different substrates, while fungi, such as basidiomycetes, can occur on the same substrate as these plants and sometimes associate with them. In Brazil, there are few studies with bryofilated Agarycomycetes and they rarely identify the mosses or the liverworts involved in this association. Taxonomic studies involving bryophyte fungi and the bryophytes involved could demonstrate the ecological relationship and help in the conservation efforts of these groups. This study aimed to investigate the biodiversity and associations of Agaricales (Fungi, Agaricomycetes) and bryophytes in a portion of the Atlantic Forest biome in the state of Rio Grande Sul, southern Brazil. The São Francisco de Paula National Forest (FLONA - SFP) is a preserved high and humid environment and was selected to carry out the collections. Our study described for the first time the true association with microscopic evidence between Gerronema stuckertii and Campylopus pilifer, Galerina stylifera, Campylopus julicaulis and Chlorella sp., Oudemansiella platensis and Metzgeria consanguinea, Psathyrella murrilli and Brachythecium sp. With regard to biological diversity in Brazil, this study improves the understanding of associations between mosses and fungi.